Evaluación de los mecanismos de participación ciudadana en la toma de decisiones del GAD Chone período 2013- 2017. - Anchundia Cevallos, Carmen Elena (2018)
The Constitution of Ecuador establishes that Citizen Participation is a right where people can intervene in the different decisions that a municipal entity considers necessary. The GAD of the canton Chone promotes the intervention of citizens through an ordinance that is bound to comply with the requirements of the same; In the development of the research, the participation of citizens in making dispositions regarding public interest issues was evaluated, defining as objective to evaluate the mechanisms of citizen participation of the GAD and identify the public regulatory policies that apply to be compared with the laws that promote citizen participation. In the same way, for the development of the corresponding study, activities were determined denoting the fulfillment of the social actors; then a comparative matrix of the laws that promote citizen participation was made with the ordinance of the GAD of the canton Chone, in this way an interview was applied to the head of the department specifying the mechanisms and strategies used to fulfill the activities, on the other On the other hand, the applied survey managed to obtain relevant results, which allowed knowing the shortcomings and strengths of those involved, since only 3 mechanisms are applied, showing a deficiency of noncompliance with the law; for this reason, an improvement plan was developed where citizens are encouraged to participate in the decision making of the GAD, considering that these activities are important for there to be a commitment to public management based on transparency and citizen participation.